2006
DOI: 10.1111/j.1471-4159.2006.04090.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical distribution and biochemical characterization of the novel RFamide peptide 26RFa in the human hypothalamus and spinal cord

Abstract: 26RFa is a novel RFamide peptide originally isolated in the amphibian brain. The 26RFa precursor has been subsequently characterized in various mammalian species but, until now, the anatomical distribution and the molecular forms of 26RFa produced in the CNS of mammals, in particular in human, are unknown. In the present study, we have investigated the localization and the biochemical characteristics of 26RFa-like immunoreactivity (LI) in two regions of the human CNS -the hypothalamus and the spinal cord. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 65 publications
(152 reference statements)
2
87
0
2
Order By: Relevance
“…26RFa is a neuropeptide initially known to be produced by hypothalamic neurons (1,4,5) that cannot be responsible for the robust concentrations of the peptide detected in the blood (present data and 22). The observation that oral glucose load results in an increase of plasma 26RFa, as observed for incretins, suggested that the gastrointestinal tract may produce 26RFa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…26RFa is a neuropeptide initially known to be produced by hypothalamic neurons (1,4,5) that cannot be responsible for the robust concentrations of the peptide detected in the blood (present data and 22). The observation that oral glucose load results in an increase of plasma 26RFa, as observed for incretins, suggested that the gastrointestinal tract may produce 26RFa.…”
Section: Discussionmentioning
confidence: 97%
“…26RFa and its N-extended form 43RFa (also referred to as QRFPs) are RFamide peptides discovered in the brain of various vertebrate species and identified as the cognate ligands of the human orphan G-protein-coupled receptor GPR103 (1)(2)(3)(4)(5)(6). Neuroanatomical observations revealed that 26RFa-and GPR103-expressing neurons are primarily localized in hypothalamic nuclei involved in the control of feeding behavior (1,2,5,7).…”
mentioning
confidence: 99%
“…HPLC analysis combined with RIAs indicated the existence of both 26-and 43-amino acid residue RFamide peptide-like immunoreactivities in the hypothalamus and spinal cord of humans (Bruzzone et al 2006). Indeed, an N-terminally extended peptide of 43 residues, called 43RFa or QRFP, has been characterized in rat brain extracts, as well as in PC12 cells and the culture medium of CHO cells that express the human precursor, as described above (Fukusumi et al 2003, Bruzzone et al 2006, Takayasu et al 2006; Fig.…”
Section: Unity and Diversity Of The Structure Of 26rfa/qrfp In Vertebmentioning
confidence: 93%
“…A number of immunohistochemical studies that used antisera against FMRFamide suggested that the nervous system of vertebrates also contained neuropeptides immunologically related to FMRFamide (Raffathe neuropeptide FF (NPFF) group, the prolactin-releasing peptide (PrRP) group, the gonadotropin-inhibitory hormone (GnIH) group, the kisspeptin group, and the 26RFa/QRFP group (for reviews, see Ukena & Tsutsui (2005), Bruzzone et al (2006), Osugi et al (2006), , Tsutsui (2009), Tsutsui et al (2010a,b), Chartrel et al (2011), Leprince et al (2013); Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Both peptides were identified as the cognate ligands of the orphan G-protein-coupled receptor 103 (GPR103) (6,7). In humans and rodents, 43RFa, 26RFa, and GPR103 are mainly expressed in brain, particularly in the hypothalamus (8), as well as in peripheral tissues, including the eye, testis, thyroid, adipose tissue, and macrophages (6,(9)(10)(11). 43RFa and 26RFa have been implicated in many physiological functions, including stimulation of food intake (5,(12)(13)(14)(15)(16)(17), regulation of gonadotropic axis (18,19), aldosterone secretion (7,20), bone formation (21), adipogenesis and inflammation (10,11), blood pressure (12), and prostate cancer differentiation and migration (22).…”
mentioning
confidence: 99%